The Association Between Smartphone Addiction and Sleep: A UK Cross-Sectional Study of Young Adults - Sohn, Sei Yon; Krasnoff, Lauren; Rees, Philippa; Kalk, Nicola J.; Carter, Ben (Frontiers in Psychiatry, 2021)
Abstract Background In a large UK study we investigated the relationship between smartphone addiction and sleep quality in a young adult population. Methods We undertook a large UK cross-sectional observational study of 1043 participants aged 18 to 30 between January 21st and 30th February 2019. Participants completed the Smartphone Addiction Scale Short Version, an adapted Pittsburgh Sleep Quality Score Index and reported smartphone use reduction strategies using both in-person (n=968) and online (n=75) questionnaires. A crude and adjusted logistic regression was fitted to assess risk factors for smartphone addiction, and the association between smartphone addiction and poor sleep. Results 1071 questionnaires were returned, of which 1043 participants were included, with median age 21.1 (interquartile range (IQR) 19-22). 763 (73.2%) were female, and 406 reported smartphone addiction (38.9%). A large proportion of participants disclosed poor sleep (61.6%), and in those with smartphone addiction, 68.7% had poor sleep quality, compared to 57.1% of those without. Smartphone addiction was associated with poor sleep (aOR=1.41, 95%CI:1.06-1.87, p=0.018). Conclusions Using a validated instrument, a large minority of young adults reported smartphone addiction. Smartphone addiction was associated with poor sleep, independent of duration of usage, indicating that length of time should not be used as a proxy for harmful usage. Funding The study was not funded